Investigating Brand Switching on Cosmetics Products: A Case Study of Nu Skin - Mayong Ajiwinanto; Megawati Simanjuntak; Hendri Tanjung (Binus Business Review, 2021)
The rapid development of the cosmetics industry and the high competition in the cosmetics market in Indonesia impact consumers. The market has many available choices of cosmetics products, and this situation causes many consumers to switch brands. The research aimed to analyze the suitability of Sharia about cosmetics products from Nu Skin and the factors that influenced the brand switching of the cosmetics product with multi-level marketing. The research applied a quantitative and descriptive approach. Data collection from respondents was carried out with a structured questionnaire. The respondents were consumers who had bought and used Nu Skin products. Around 150 respondents were selected through the purposive sampling method. Then, the researchers used the LISREL software. The connection between the variables was investigated by Structural Equation Modeling (SEM). The ï¬ndings indicate that Word of Mouth (WOM) and marketing mix significantly influence the brand image of the cosmetics products. Similarly, religiosity and marketing mix have a significant influence on brand attitude. Then, brand image and brand attitude have a significant effect on brand switching. However, religiosity has no significant effect on brand switching. For marketing practitioners, the results can be considered in terms of marketing strategy in consumersâ€™ habits of accessing social media to read product reviews from their friends who have used Nu Skin products before. The more people review and recommend the products to others, the higher the consumersâ€™ interest is in buying Nu Skin products, and the smaller the intensity is involved in brand switching behavior. The research offers a new insight regarding the inï¬‚uencing factors of brand switching of halal cosmetics products through multi-level marketing.